Accelerated hydrothermal degradation and biodegradation of electrospun polycaprolactone montmorillonite nanofiber membrane - Dela Cruz, Michael Leo; Bornillo, Kristal Aubrey; Riña, John Jaymar; Diaz, Leslie Joy (Philippine Engineering Journal [eJournal])
The nano composite of montmorillonite (MMT) clay and polcyaprolacttone (PCL) have been reported to successfully serve as a reusable adsorbent of heavy metal from wastewater from metal extraction. In this study, the degradability of the electrospun polycaprolactone (PCL) nano fiber membrane, as support material to MMT, was evaluated through accelerated hydrothermal degradation and biodegradation as a continuous effort to be able to appropriately discard the spend adsorbent materials. In the hydrothermal conditions, the membranes were immersed in NaOH solution and H2O at 35 degree Celsius and 45 degree Celsius at specific durations. While for the biodegradation, alkali-treated and untreated membranes were buried in two separate media, i.e. soil and compost, to evaluate the natural decomposition. The extent of degradation measured via gravimetry showed that the alkali-treated membranes subjected to hydrothermal degradation had the highest weight loss that ranged from 27% to 96% after 24 hours of immersion. The membranes buried in compost had weight loss ranging from 77% up to 100% after three (3) weeks of being in the ground. Compared to membrane made of pristine PCL polymer, it was also shown that MMT improved the degradability of the membrane such that 96% of weight loss was already observed after 24 hours of hydrothermal immersion and 100% weight loss after three (3) weeks of ground covering. This could have been brought about by the decrease in the degree of crystallinity of the support polymer which was almost 30% lower compared to the pristine material. It was also found that biodegradation in compost was better than in soil such that a maximum weight loss of 100% in compost was observed compared to 70% weight loss in soil after 3 weeks. The former was found to contain 180 times more microorganisms than soil which could be responsible for the higher biodegradation performance. These results would be useful in establishing protocols for the disposal of PCL and its derivatives after being used in various applications not just in wastewater treatment but also in other applications like biomedical devices in the medical industry.